PERBANDINGAN METODE ANALISIS KAPASITAS LENTUR DAN FAKTOR REDUKSI PELAT COMBIDECK TERHADAP UJI LABORATORIUM - hariadi yuliantoo (TEKNISIA, 2018)
Combideck slab was a floor slab that used a steeldeck as positive reinforcement and as formwork that hold the flooring concrete cast. While combined with wiremesh as negative reinforcement, the combideck system even more efficient than half slab casting method for concrete flooring system (Siregar, 2010). However, there is no standard method in Indonesia to analyze the flexure capacity of combideck. This study compared 3-analysis method (ultimate, working stress and SDI-ANSI) to laboratory test result that already done by Kadir&Sudarmadi (2008). Based on the published data, this study analyzed the combideck section properties to determine the theoretical flexure capacity, than it compared to the test result for validation. Besides that, this study also evaluated the reduction factor from the all 3 method to laboratory test result. This study validated that the working stress and SDI-ANSI method were accurate to analyze the slip flexure capacity, but the ultimate method was accurate for maximum flexure capacity. Because of the theoretical capacity form all 3 method was slightly greater than the test result (SDI-ANSI= 5.79%, working stress= 4.83%, ultimate method = 5.72%), the reduction factor from this study resulted as =0.76.